Ius cogens human rights. The absolute right regarding prohibition of torture and the related interpretations, with particular consideration to the reservations of the United States - Takács, Izolda (Pedagogika Społeczna Nova, 2022)
The following paper attempts to introduce the general characteristics of the concept of torture and to describe it both as human right and criminal act. I will furthermore address the specific interpretation of the USA with regards to their reservation towards the Convention against Torture and Other Cruel, Inhu- man or Degrading Treatment or Punishment (UNCAT). Finally, the paper delineates the accountability of member states and the two methods applied to survey and prevent infringements.